Invigilator system for UMP examination problem based on Faculty of Computer System & Software Engineering (FSKKP) - Noor Khairunnisa, Mat Yusof (2015)
The main problem faced by the colleges or universities around the world are monitoring task in the examination schedule. This is the most serious problems and conflicts in a supervisory role in the examination schedule. Among the main factors in this problem is the size of exam rooms, the number of days within the constraints of the examination, the structure and these factors different from one another. This problem also occurs in the FSKKP, UMP. This is because there is a sense of dissatisfaction with the exam schedule is given and the amount of surveillance between overseers assigned to the supervision of the examination. Instead, they suggested that they have the task of monitoring the distance constraints like at least two or three day gap. They would be happy if the given task is less supervision. This is because they have to provide or to mark their own paper. Here, we help solve problems in carrying out surveillance during the examination at the Faculty of Computer Systems and Software Engineering (FSKKP), Universiti Malaysia Pahang, based on the requirements required by the FSKKP. Finally, to achieve the goal of developing an efficient system for the preparation of a systematic surveillance scheduling heuristics used. Methods graph heuristic used in their surveillance schedule. The graph heuristic used by the invigilators because it is one method that is easy to understand and easy to use. To develop this system we use a number of software and hardware. The software used is as XAMP, PHP, MYSQL, Adobe Dreamweaver, and Apache Web Server. The hardware used was as computers, hard disk, and pen drive. In addition, we made studies on several universities. We also made a study and survey of some programming techniques used to develop this system.